Empowering the powerful: a critical discourse analysis of public discourse on graduate employability - Mohd Noor, Siti Noor Fazelah (2015)
This study explores the issue of graduate employability in Malaysia as construed in public discourse in English, a language of power in Malaysia. The term employability itself has many definitions depending on the requirements of government and industry, and in the case of Malaysia, the English-language ability of graduates is inseparable from graduate employability. Data were collected from three socially significant English-language publications: a mainstream newspaper (the New Straits Times), an alternative newspaper (The Malaysian Insider), and a government document outlining the national approach to improving graduate employability in universities (the Graduate Employability Blueprint). The data were collected between 2012 and 2013, a significant two-year period of time due to the publication of the Graduate Employability Blueprint in 2012, and the five-yearly Malaysian General Election in 2013. Applying Critical Discourse Analysis (Fairclough, 1995), the study employs Transitivity analysis (Halliday & Matthiessen, 2004) and Appraisal analysis (Martin & White, 2005) from Systemic Functional Linguistics. The analysis looks at the grammatical roles and evaluation of important social actor groups in the graduate employability issue (e.g. government, government link companies, employers, graduates, parents and teachers). The findings show that government, the government programs and the employers are construed favourably, while the graduates are depicted unfavourably. Parents and teachers are largely excluded from the discourse. Significant government expenditure and national resources from public and private organizations are dedicated to improving the employability of graduates in Malaysia. However,the public discourse on graduate employability in the powerful English language appears unlikely to contribute to a social context where the aims of the groups with a key interest in graduate employability will be achieved.